Iodine-catalyzed synthesis of 5H-phthalazino[1, 2-b]quinazoline and isoindolo[2, 1-a]quinazoline derivatives via a chemoselective reaction of 2-aminobenzohydrazide and 2-formylbenzoic acid in ionic liquids. Issue 23 (8th June 2016) - Jin, Rong-Zhang; Zhang, Wen-Ting; Zhou, Yu-Jing; Wang, Xiang-Shan
Graphical abstract: Highlights: It is a chemoselective reaction to challenge a carboxyl group with two amino groups. The products depend on the steric effect in the reactant of 2-aminobenzohydrazides. It provides an efficient method for the synthesis of fused polycyclic heterocycle. Abstract: A chemoselective reaction of 2-aminobenzohydrazides and 2-formylbenzoic acid is described for the synthesis of 5 H -phthalazino[1, 2- b ]quinazoline and isoindolo[2, 1- a ]quinazoline derivatives in ionic liquids catalyzed by iodine. It is found that the type of the products depends on the steric effect in the reactant of 2-aminobenzohydrazides.